POLLEN STRUCTURE IN SELECTED SPECIES OF MAHARAJA KRISHNAKUMASINHJI BHAVNAGAR UNIVERSITY, BHAVNAGAR DISTRICT, GUJARAT STATE, INDIA (International Association of Biologicals and Computational Digest, 2022)
Palynology, scientific discipline concerned with the study of plant pollen. Pollens are male reproductive cells in plants, very tiny grains produced by the stamens of flower. Pollen represents the land flora and can be used in many different disciplines. Pollen can be used to determine pollination mechanisms, therapeutic activity and source zone of pollinators. The present investigation deals with the study of pollen taxa of Twenty (20) species of Maharaja Krishnakumasinhji Bhavnagar University, Bhavnagar, and Gujarat, India. These pollen taxa belong to seventeen (17) different families. The pollen of these families has diversity in morphological characters viz, shape, attachment of filament, type of pollen and ornamentation. This study provides Palynological data of pollen taxa, which will helpful in future
Keywords: Pollen structure, shape, Palynology, Bhavnagar